Risk factors associated with the incidence and recurrence of hyperkalaemia in patients with cardiorenal conditions. Issue 4 (5th January 2021) - Tafesse, Eskinder; Hurst, Michael; Hoskin, Louise; Badora, Karolina; Sugrue, Daniel; Qin, Lei; James, Glen; McEwan, Phil
Abstract: Introduction: Hyperkalaemia (HK) is associated with increased mortality risk. Prior studies suggest that the causes of HK are multifactorial. This study aimed to examine risk factors for incident and recurrent HK in six large real‐world cohorts of UK patients that could be considered at elevated HK risk because of underlying disease pathology and/or medication use. Methods: This retrospective, observational cohort study utilised UK primary and secondary care data from Clinical Practice Research Datalink (CPRD) and linked Hospital Episode Statistics (HES), respectively. Patients were included if they were aged ≥18 years and had a record of ≥1 condition of interest (chronic kidney disease [CKD] stage 3+, heart failure, resistant hypertension [RHTN], dialysis, diabetes) and/or renin‐angiotensin‐aldosterone system inhibitors (RAASi) use between 01 January 2003 and 30 June 2018. Based on their diagnosis/ RAASi prescription record, patients were assigned to overlapping cohorts. The outcomes assessed were HK and recurrent HK, the latter defined as second or subsequent HK episode during follow‐up. HK was defined as a serum K + measurement ≥5.0 mmol/L; thresholds of ≥5.5 and ≥ 6.0 mmol/L were also explored. Results: Of 931 460 meeting the eligibility criteria, 310 535 (33.3%) patients experienced ≥1 HK event and 187 719 (20.2%) experienced HK recurrence. The probability of subsequent HK events increased with event number from 60.5% for the second event to 76.5% for the sixth and the corresponding time to the next HK event decreased from 15.8 months to 6.1 months. Amongst the key risk factors, serum creatinine, serum phosphorus, systolic blood pressure, and white cell count demonstrated direct relationships with incidence and recurrence of HK, while inverse relationships were observed for estimated glomerular filtration rate (eGFR), haemoglobin and diastolic blood pressure. The relationship for Charlson's Comorbidity Index was mixed. The use of RAASi and anti‐hyperglycaemic agents was associated with an increased risk of HK, while the use of diuretics (non‐K + ‐sparing) was protective against HK. Conclusion: Several risk factors for HK that are easily measured in routine clinical practice were identified, facilitating the identification of patients who are at the highest risk of experiencing HK, including recurrent HK.